A Hooded Crow - Thomas, Craig; 1942-2011 (London Fontana, 1992)
Lays bare the continuing suspicions and rivalries of the post Cold War atmosphere in Eastern Europe in a story of illegal arms dealing and its implications for the time bomb that is South Africa. Craig Thomas is the author of "The Bear's Tears" and "The Last Raven"
Keywords: Africa -- Europe -- Spy stories